Myeloperoxidase in Hypertensive Disorders of Pregnancy and Its Relation with Nitric Oxide - Rocha-Penha, Lilliam [UNESP]; Caldeira-Dias, Mayara [UNESP]; Tanus-Santos, José Eduardo; De Carvalho Cavalli, Ricardo; Sandrim, Valéria Cristina [UNESP] (Wolters Kluwer, 2017)
Elevated levels of myeloperoxidase have been demonstrated in women with preeclampsia where it may contribute to endothelial dysfunction mediated, in part, by nitric oxide impairment. In this study, we investigated myeloperoxidase in hypertensive disorders of pregnancy and its contribution to the impairment of the vasodilator nitric oxide. We found higher levels of myeloperoxidase in supernatant from human umbilical vein endothelial cells cultures incubated with plasma from preeclampsia group compared with healthy pregnant women. Further, we measured plasma concentration and activity of myeloperoxidase in 219 healthy pregnant women, 130 gestational hypertension (on antihypertensive therapy or not), and 143 preeclampsia patients (on antihypertensive therapy or not). We found that patients with preeclampsia and gestational hypertension without antihypertensive treatment showed higher levels and activity of this enzyme, respectively. Moreover, the inhibition of myeloperoxidase activity in vitro improved nitric oxide bioavailability. Our results indicate a higher cardiovascular risk in pregnant women with hypertensive disorders, and that active myeloperoxidase may play a role in endothelial dysfunction in these conditions by impairment of nitric oxide availability. Besides, the use of antihypertensive drugs seems to decrease enzyme levels suggesting a new protective feature for these drugs.
Keywords: cardiovascular diseases; heparin; human umbilical vein endothelial cells; nitric oxide; pregnancy